The Introduction of English-Induced Neologisms in Spanish Tweets: A Case-Study on covidiota - Kailich, Franziska (Frontiers in Communication, 2022)
This paper intends to trace the introduction of an English-induced, COVID-related neologism, covidiota, into the Spanish language. The study is based on a corpus of tweets, starting in March 2020.